Transformasi Digital UMKM melalui Strategi Social Media Marketing - Abdul Khalik; Abdul Chalel Rahman (CV. ITTC INDONESIA, 2025)
The rise of social media usage in the digital era has transformed marketing patterns, especially for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the Social Media Marketing (SMM) strategies applied by Auva Store to increase sales and expand market reach. A qualitative descriptive approach was employed, using in-depth interviews and social media content documentation as data collection methods. The results indicate that the organic use of platforms such as Facebook, Instagram, and WhatsApp has enabled more effective communication with customers, increased brand awareness, and strengthened customer loyalty. The key strategies include influencer endorsements, sales promotions, direct communication, and affiliate marketing. Despite these efforts, the store's social media engagement—measured by likes, comments, and shares—remains low, suggesting the need to improve content quality, visual appeal, and message clarity. These findings emphasize the importance of digital communication strategies in enhancing customer interaction. The study concludes that well-planned and consistent SMM can serve as a critical success factor for MSMEs to remain competitive and sustainable in the digital marketplace.